Integration Strategy for Kambang and Tangkahan Fish Landing Bases - Adzandi, Facjri Restu; ., Mustaruddin; Wisudo, Sugeng Hari; Muninggar, Retno (Engineering And Technology Journal, 2024)
The Kambang Fish Landing Base is a Type D port (with a service capacity of 2,000 tonnes per year).The fish production of PPI Kambang is the highest in Pesisir Selatan Regency with an existing fishing potential of 1038.15 tonnes, but there will be a decline to 138,832 tonnes by 2022. In 2019, the Pesisir Selatan Regency Government will receive IDR 2 billion in local revenue (PAD) from PP Kambang's operations from ship services and port services. The presence of tangkahans around fishing ports, as happened at PP Kambang, is seen as a cause of 'disruption' to the operation and performance of fishing ports. It is feared that the port will not function, which could disrupt fisheries management in the West Sumatra region. This research aims to identify the root causes of some of the fishing fleets in the PPI Kambang area not landing their catches at PPI Kambang and integration strategies so that catchments around the PPI Kambang area with PPI Kambang in an effort to realise capture fisheries governance that supports the creation of sustainable fisheries. The research was conducted in the PPI Kambang Fish Landing Base Harbour and surrounding Tangkahan in Pesisir Selatan Regency, West Sumatra Province. Test results using SEM analysis show the potential for synergy between PPI Kambang and Tangkahan in terms of supply, landing, production and marketing activities. However, several functional facilities at PPI are still not functioning and need to be repaired and maintained